Mathematical model of dynamic systems gas turbine engine diagnostics "diagnosis - quality - reliability" - Чоха, Ю.М. (Proceedings of National Aviation University (archive), 2006)
The conceptual new approach is motivated to process of the diagnostics gas-turbine engine with use the complex diagnostic factors quality and reliability for taking the working decision.